A new approach for analysing interdiffusion in multicomponent alloys. (November 2021) - Belova, Irina V.; Afikuzzaman, Mohammad; Murch, Graeme E.
Abstract: Analysis of interdiffusion in multicomponent alloys is addressed by developing a new and elegant mathematical approach that is based on the fitting of composition profiles into a closed-form solution where interdiffusion coefficients are independent of composition. As examples, ternary metallic systems are analysed using one and two diffusion couples with the full set of interdiffusion coefficients being determined. Overall, the new fitting method gives excellent outcomes and allows the probing of multiple solutions (validated by back-testing) that exist when a single diffusion couple is used in multicomponent (>2) systems. Important findings of the present investigation show that small differences in composition profiles may lead to large differences in the interdiffusion coefficients. In addition, the newly developed approach is successfully applied to experimental results for the Cu-Ni-Zn alloys annealed at 775 °C for 48 h. Graphical abstract: Image, graphical abstract